Observation of dielectric dispersion and relaxation behavior in Ni2+-substituted cobalt ferrite nanoparticles. Issue 9 (3rd February 2022) - Srinivasamurthy, K. M.; El-Denglawey, A.; Manjunatha, K.; Angadi V., Jagadeesha; Oliveira, M. C.; Longo, E.; Lázaro, S. R.; Ribeiro, R. A. P.
Abstract : Combined experimental and theoretical analysis reveals the superior properties of Co1− x Ni x Fe2 O4 nanoparticles – a putative candidate for energy-harvesting applications. Abstract : In this study, a joint theoretical and experimental approach was employed to investigate the structural, electronic, magnetic and dielectric properties of novel ferrite (CNF) Co1− x Ni x Fe2 O4 ( x = 0.0, 0.25, 0.5, 0.75 and 1.0) nanoparticles obtained using a low-cost combustion synthesis technique. Structural analysis indicated the single-phase formation of synthesized ferrite with a cubic spinel structure. Rietveld refinement was performed to estimate the lattice constant, strain and cationic distances. Vibrational Raman spectroscopy was employed to further confirm the monophasic cubic spinel structure with inverse cation distribution associated with the increase of the T 2g (2) Raman mode, evidencing the presence of different cations at octahedral sites. The real part of the dielectric constant ( ε ′) and the dielectric loss tangent (tan δ ) were explored as a function of frequency, and the Nyquist complex impedance plots of all the samples were studied. The electrical properties of the samples at room temperature demonstrated the dispersion behavior associated with Maxwell–Wagner interfacial polarization mechanism and the hopping of charge carriers. DFT calculations complemented the experimental characterization, indicating a ferrimagnetic ground state for all models associated with band gap increases and dielectric constant reduction with an increasing amount of Ni. The low dielectric loss with Ni 2+ substitution at higher frequencies makes CNF a promising candidate in the electronics industry for energy-harvesting devices.